Cross-cultural adaptation and psychometric evaluation of the Engaged Teachers Scale among Arabic-speaking physical education teachers - Boukari, Samia; Guelmami, Noomen; Chalghaf, Nasr; Ceylan, Halil İbrahim and Stefanica, Valentina and Mekni, Rim and Dhahbi, Wissem and Dergaa, Ismail (Frontiers in Education, 2025)
BackgroundTeacher engagement is a positive psychological state characterized by vigor, dedication, and absorption in professional activities, representing the opposite of burnout. While research has established the importance of engagement for teacher effectiveness, wellbeing, and student outcomes, validated measurement tools for assessing engagement among physical education teachers in Arabic-speaking contexts are lacking. This study addresses this gap by adapting a widely used engagement scale to the cultural and professional context of Arabic-speaking physical education teachers.ObjectiveTo adapt and evaluate the psychometric properties of the Engaged Teachers Scale for Arabic-speaking physical education teachers.MethodThe study involved 621 physical education teachers recruited in two phases: exploratory (n = 182) and confirmatory (n = 439). Participants completed an Arabic translated version of the Engaged Teachers Scale (A-ETS) and the Teacher Physical Education Job Satisfaction Inventory (TPEJSI). The exploratory sample included 44.2% female and 55.8% male teachers (mean age = 40.15 years), while the confirmatory sample comprised 45.8% female and 54.2% male teachers (mean age = 33.06 years). Teaching experience across both samples ranged from less than 5 years to more than 15 years. Factor structure was assessed through exploratory and confirmatory factor analysis, while reliability was evaluated using Cronbach’s alpha and item-total correlations.ResultsThe four-factor structure of the original scale was preserved in the Arabic version, explaining 77.51% of the total variance. Confirmatory factor analysis indicated excellent model fit for both first-order (χ2 = 174.83, df = 98, CFI = 0.98, RMSEA = 0.04) and second-order (χ2 = 90.91, df = 101, CFI = 0.98, RMSEA = 0.045) models. Internal consistency was strong for all dimensions, with Cronbach’s alpha coefficients ranging from 0.88 to 0.89. Moderate positive correlations between A-ETS dimensions and TPEJSI factors supported the concurrent validity of the scale. While these correlations are modest in magnitude, they are theoretically consistent and statistically significant, indicating appropriate discriminant validity between engagement and satisfaction constructs.ConclusionThe Arabic version of the Engaged Teachers Scale demonstrates robust psychometric properties, confirming its validity and reliability for assessing engagement among physical education teachers in Arabic-speaking educational settings. This validated instrument enables further research on teacher engagement and its relationships with professional outcomes and student achievement in physical education contexts.